2016
DOI: 10.1007/s13224-016-0950-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spot Urinary Albumin–Creatinine Ratio as Screening Tool in Prediction of Pre-eclampsia in Early Pregnancy

Abstract: Spot urinary ACR values are higher in asymptomatic women in early pregnancy, who developed pre-eclampsia later on. When measured early in the second trimester, an ACR ≥ 35.5 mg/mmol predicted pre-eclampsia well before the onset of clinical manifestations with high sensitivity and specificity. It can be used as a good screening tool for predicting pre-eclampsia in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…11,12 The sensitivity of spot UPCR at the cut-off value of ≥ 35.5 mg/mmol as a screening test to predict preeclampsia in our study was found to be 80% which is comparable to the studies done by Baweja et al, (83.3%), Fatema et al, (80%) and Mishra et al, (87.5%). [11][12][13] In the present study abnormal uterine artery doppler indices (RI > .0.7/PI > 1.4/ presence of diastolic notch) were associated with increased risk of developing preeclampsia in later part of pregnancy. The cut-off value of RI and PI was similar with the study of Sahoo et al 14 Razieh DF et al, found that 23 pregnancies (85.2%) with preeclampsia had RI more than 0.7 and only 4 (14.8%) had RI < 0.7 (p = 0.001).…”
Section: Discussionsupporting
confidence: 50%
“…11,12 The sensitivity of spot UPCR at the cut-off value of ≥ 35.5 mg/mmol as a screening test to predict preeclampsia in our study was found to be 80% which is comparable to the studies done by Baweja et al, (83.3%), Fatema et al, (80%) and Mishra et al, (87.5%). [11][12][13] In the present study abnormal uterine artery doppler indices (RI > .0.7/PI > 1.4/ presence of diastolic notch) were associated with increased risk of developing preeclampsia in later part of pregnancy. The cut-off value of RI and PI was similar with the study of Sahoo et al 14 Razieh DF et al, found that 23 pregnancies (85.2%) with preeclampsia had RI more than 0.7 and only 4 (14.8%) had RI < 0.7 (p = 0.001).…”
Section: Discussionsupporting
confidence: 50%
“…The single criteria for inclusion in the study were the presence of diagnosed SLE according to the American College of Rheumatology 1997 criteria. 7 The exclusion criteria included the presence of any kidney disease with other etiology like diabetes, pregnant women, and thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…This value was significantly higher in pre-eclamptic patients (p<0.001). According to our reference study 14 , the cutoff value for urinary albumin to creatinine ratio was taken as 35.5 mg/mmol. (Table-I) Over all, the test was positive in forty seven (23.5%) patients and negative in the remaining one hundred and fifty three (76.5%) patients ( Table-II).…”
Section: Resultsmentioning
confidence: 99%